Micromonas versus virus: New experimental insights challenge viral impact. (18th April 2017) - Ruiz, Eliana; Baudoux, Anne‐Claire; Simon, Nathalie; Sandaa, Ruth‐Anne; Thingstad, T. Frede; Pagarete, António
Summary: Viruses have recurrently been hypothesized as instrumental in driving microbial population diversity. Nonetheless, viral mediated co‐existence of r/k‐strategists, predicted in the Killing‐the‐Winner (KtW) hypothesis, remains controversial and demands empirical evidence. Therefore, we measured the life strategy parameters that characterize the relevant system Micromonas ‐Micromonas Virus (MicV). A large number of host and viral strains (37 and 17, respectively) were used in a total of 629 cross‐infectivity tests. Algal and viral abundances were monitored by flow cytometry and used to calculate values of growth rate, resistance capacity, and viral production. Two main assumptions of the KtW model, namely (1) a resistance‐associated cost on growth and (2) a negative correlation between resistance and viral production capacity, were mildly observed and lacked statistical significance. Micromonas strains infected by more MicV strains presented higher lysis and viral production rates as the number of infectious virus strains increased, suggesting a 'one‐gate' regulation of infection in this system. MicV strains demonstrated a vast range of virion production capacity, which unexpectedly grew with increasing host‐range. Overall, the significant trends observed in here demonstrate strong co‐interactions at different levels between Micromonas and MicV populations, however, the role of viruses as major driving force in phytoplankton fitness wasn't explicitly observed.